CompTIA PenTest+ PT0-002 Cert Guide, 2nd Edition - Santos, Omar (Pearson IT Certification, 2021)
This is the eBook edition of the CompTIA PenTest+ PT0-002 Cert Guide. This eBook does not include access to the Pearson Test Prep practice exams that comes with the print edition. Learn, prepare, and practice for CompTIA PenTest+ PT0-002 exam success with this CompTIA PenTest+ PT0-002 Cert Guide from Pearson IT Certification, a leader in IT Certification learning. CompTIA PenTest+ PT0-002 Cert Guide presents you with an organized test preparation routine through the use of proven series elements and techniques. Do I Know This Already? quizzes open each chapter and allow you to decide how much time you need to spend on each section. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. CompTIA PenTest+ PT0-002 Cert Guide focuses specifically on the objectives for the CompTIA PenTest+ PT0-002 exam. Leading security expert Omar Santos shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. This complete study package includes A test-preparation routine proven to help you pass the exams Do I Know This Already? quizzes, which allow you to decide how much time you need to spend on each section Chapter-ending exercises, which help you drill on key concepts you must know thoroughly An online interactive Flash Cards application to help you drill on Key Terms by chapter A final preparation chapter, which guides you through tools and resources to help you craft your review and test-taking strategies Study plan suggestions and templates to help you organize and optimize your study time Well regarded for its level of detail, assessment features, and challenging review questions and exercises, this official study guide helps you master the concepts and techniques that ensure your exam success. This study guide helps you master all the topics on the CompTIA PenTest+ PT0-002 exam, including Planning and Scoping a Penetration Testing Assessment Information Gathering and Vulnerability Identification Social Engineering Attacks and Physical Security Vulnerabilities Exploiting Wired and Wireless Networks Exploiting Application-Based Vulnerabilities Cloud, Mobile, and IoT Security Performing Post-Exploitation Techniques Reporting and Communication Tools and Code Analysis.